Feminization of poverty and problem-solving capacity among female-headed households in indonesia: self-esteem and social support as determinants - Bambang Rustanto; Tuti Kartika; Dwi Yuliani; Didiet Widiowati; Ayi Haryani; Aryohaji Istyawan (Indonesian Institute for Counseling, Education and Theraphy, 2026)
Female-headed households represent one of the most economically and psychosocially vulnerable groups in Indonesia; however, their internal coping capacities remain insufficiently explored within the social welfare literature. This study investigates how self-esteem and social support shape the problem-solving capacity of poor female-headed households in Bandung Regency, West Java, Indonesia. A qualitative descriptive-explanatory case study design was employed, with data gathered through in-depth interviews with ten purposively selected primary informants prioritizing information-rich cases, two focus group discussion sessions, and participant observation. Data were analyzed using theory-guided thematic analysis following the interactive model of Miles, Huberman, and Saldaña, and validated through source triangulation and member-checking procedures. The findings reveal that informants experienced a severe collapse of self-esteem and social misrecognition during the initial transition following spousal loss, further exacerbated by stigma within patriarchal rural communities. Active involvement in the Pekka Union served as a radical psychosocial turning point, reconstructing self-esteem through collective recognition and skill mastery. Social support emerged as the most dominant force shaping problem-solving capacity, substantially exceeding the contribution of self-esteem. These findings challenge deficit-oriented perspectives and affirm that resilience among female-headed households is relational and collectively constructed. Social welfare interventions should therefore adopt strengths-based and feminist empowerment strategies.